MAINGUENEAU, Dominique. Enunciados aderentes. Tradução de Sírio Possenti. São Paulo: Parábola, 2022, 192 p. - Matos, José Wesley Vieira; Mendes, Maria das Dores Nogueira (Bakhtiniana. Revista de Estudos do Discurso, 2023)
Resenha